Finding of Agr Phase Variants in Staphylococcus aureus - Vishal Gor; Aya J. Takemura; Masami Nishitani; Masato Higashide; Veronica Medrano Romero; Ryosuke L. Ohniwa; Kazuya Morikawa (mBio, 2019)
ABSTRACT Staphylococcus aureus is an important human pathogen whose success is largely attributed to its vast arsenal of virulence factors that facilitate its invasion into, and survival within, the human host. The expression of these virulence factors is controlled by the quorum sensing accessory gene regulator (Agr) system. However, a large proportion of clinical S. aureus isolates are consistently found to have a mutationally inactivated Agr system. These mutants have a survival advantage in the host but are considered irreversible mutants. Here we show, for the first time, that a fraction of Agr-negative mutants can revert their Agr activity. By serially passaging Agr-negative strains and screening for phenotypic reversion of hemolysis and subsequent sequencing, we identified two mutational events responsible for reversion: a genetic duplication plus inversion event and a poly(A) tract alteration. Additionally, we demonstrate that one clinical Agr-negative methicillin-resistant S. aureus (MRSA) isolate could reproducibly generate Agr-revertant colonies with a poly(A) tract genetic mechanism. We also show that these revertants activate their Agr system upon phagocytosis. We propose a model in which a minor fraction of Agr-negative S. aureus strains are phase variants that can revert their Agr activity and may act as a cryptic insurance strategy against host-mediated stress. IMPORTANCE Staphylococcus aureus is responsible for a broad range of infections. This pathogen has a vast arsenal of virulence factors at its disposal, but avirulent strains are frequently isolated as the cause of clinical infections. These isolates have a mutated agr locus and have been believed to have no evolutionary future. Here we show that a fraction of Agr-negative strains can repair their mutated agr locus with mechanisms resembling phase variation. The agr revertants sustain an Agr OFF state as long as they exist as a minority but can activate their Agr system upon phagocytosis. These revertant cells might function as a cryptic insurance strategy to survive immune-mediated host stress that arises during infection.